Dry powders for the inhalation of ciprofloxacin or levofloxacin combined with a mucolytic agent for cystic fibrosis patients. (3rd August 2017) - Akdag Cayli, Yagmur; Sahin, Selma; Buttini, Francesca; Balducci, Anna Giulia; Montanari, Serena; Vural, Imran; Oner, Levent
Abstract: Objective: This study aimed to design and characterize an inhalable dry powder of ciprofloxacin or levofloxacin combined with the mucolytics acetylcysteine and dornase alfa for the management of pulmonary infections in patients with cystic fibrosis. Methods: Ball milling, homogenization in isopropyl alcohol and spray drying processes were used to prepare dry powders for inhalation. Physico-chemical characteristics of the dry powders were assessed via thermogravimetric analysis, differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FT-IR), X-ray diffractometry and scanning electron microscopy. The particle size distribution, dissolution rate and permeability across Calu-3 cell monolayers were analyzed. The aerodynamic parameters of dry powders were determined using the Andersen cascade impactor (ACI). Results: After the micronization process, the particle sizes of the raw materials significantly decreased. X-ray and DSC results indicated that although ciprofloxacin showed no changes in its crystal structure, the structure of levofloxacin became amorphous after the micronization process. FT-IR spectra exhibited the characteristic peaks for ciprofloxacin and levofloxacin in all formulations. The dissolution rates of micro-homogenized and spray-dried ciprofloxacin were higher than that of untreated ciprofloxacin. ACI results showed that all formulations had a mass median aerodynamic diameter less than 5 μm; however, levofloxacin microparticles showed higher respirability than ciprofloxacin powders did. The permeability of levofloxacin was higher than those of the ciprofloxacin formulations. Conclusion: Together, our study showed that these methods could suitably characterize antibiotic and mucolytic-containing dry powder inhalers.